Effectiveness Test of Okra Fruit (Abelmoschus esculentus) Extract on The Growth of Trichophyton rubrum: Uji Efektivitas Ekstrak Buah Okra (Abelmoschus esculentus) Terhadap Pertumbuhan Jamur Trichophyton rubrum - Kimberly, Bella Tasya; Rini, Chylen Setiyo (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Dermatophytosis is an infectious disease of the skin caused by one of the pathogenic agents of the fungus Trichophyton. Trichophyton rubrum is a dermatophyte fungus that is included in the anthropophilic classification, where transmission occurs through direct human-to-human contact. This experiment was conducted to determine the effectiveness of giving okra fruit extract (Abelmoschus esculentus) to the growth of Trichophyton rubrum using well method, media that is used to do that is SDA (Sabouraud Dextrose Agar) with various concentrations of 25 %, 50%, 75%, 100%. Based on the results of phytochemical tests, the active compounds contained in okra fruits extract are alkaloids, flavonoids, saponins, steroid, triterpenoids, phenolics and tannins. Variations in concentration of okra fruit extract and negative control tested against Trichophyton rubrum did not show the formation of inhibition zones in the media. Meanwhile for positive control using 2% ketoconazole, an inhibition zone 35 mm was formed. This research showed that Trichophyton rubrum was resistant to okra fruit extract.